WINTGEN INEQUALITY FOR STATISTICAL SURFACES - Aydin, Muhittin Evren; Mihai, Ion (Element, 2019)
The Wintgen inequality (1979) is a sharp geometric inequality for surfaces in the 4-dimensional Euclidean space involving the Gauss curvature (intrinsic invariant) and the normal curvature and squared mean curvature (extrinsic invariants), respectively. In the present paper we obtain a Wintgen inequality for statistical surfaces.
Keywords: Wintgen inequality; statistical manifold; statistical surface; dual connections